Three essays on credit ratings - Ronchetti, Marta Allegra (2018)
This thesis focuses on preliminary ratings, studying Credit Rating Agencies (CRAs) decisions in the light of different disclosure regulations. To begin, a brief introduction provides the rationale for these studies. Chapter 1 models the strategic interaction between a monopolistic CRA and an entrepreneur. The results have three main implications. First, consistently with a strand of the literature, disclosure is not necessarily welfare improving. Second, disclosure policies and regulation cannot be a one off decision, they require tailoring and timely revisions. Thirdly, for disclosure to be effective, the rating process needs to be as accurate as possible. Chapter 2 models a competitive situation, whereby the emphasis is on the effort choice made by the CRAs. The results have a few implications. First, if financial products are complex, mandatory disclosure has no effect. Second, in bad times, mandatory disclosure gives the second contacted CRA the incentives to invest in information. Overall, disclosure never results in more information in the system. Chapter 3 fulfils the role of drawing a junction among economic literature, policy proposals and CRA regulation in order to identify the problems which have been dealt with, the successes and failures and the upcoming challenges.